Esophageal peroral endoscopic myotomy (POEM) for treatment of esophagogastric junction outflow obstruction: results from the first prospective trial - Ichkhanian, Yervant; Sanaei, Omid; Canakis, Andrew; Vosoughi, Kia; Almazan, Erik; Ghandour, Bachir; Khashab, Mouen A (Endoscopy International Open, 2020)
Background and study aims Esophagogastric junction outflow obstruction (EGJOO) is a rare esophageal dysmotility disease that is characterized by elevated integrated relaxation pressuse (IRP) with evidence of preserved peristalsis. The role of peroral endoscopic myotomy (POEM) in management of EGJOO is currently unknown.Patients and methods This is a prospective trial conducted in a single US tertiary care center from June 2015 to June 2019. Symptomatic patients, diagnosed with EGJOO on both HRM and endoluminal functional lumen imaging probe (EndoFLIP), who were eligible for POEM were recruited. Primary outcome was clinical success, defined as Eckardt score (ES) ≤ 3, at 6 months post-POEM. Other outcomes included dysphagia score, quality of life as measured by 36-item Short Form health survey scales (SF-36), post-POEM HRM, EndoFLIP, and pH measurements, and adverse events.Results A total of 15 patients (51.8 yr. 9 F) with EGJOO underwent POEM. Pre-POEM mean IRP on HRM and Distensibility index (DI) on EndoFLIP were 24.3 ± 2.2 mmHg and 1.1 ± 0.6 mm2/mmHg, respectively. Clinical success was achieved in 93 % at 6 months post-POEM. There was significant decrease in IRP (-17.6 mmHg) post-POEM. There was significant improvement at 6 months in two of the SF-36 subscales. Ten patients underwent post-POEM pH testing, seven of whom had abnormal DeMeester score. Seven patients underwent EGD evaluation revealing esophagitis in five (2 Los Angeles grade A and 3 grade B).Conclusions POEM offers a high clinical success rate for patients with EGJOO confirmed by impedance planimetry.